Chemical constituents from Neopestalotiopsis clavispora culture medium with estrogenic effects in MCF-7 cells. (December 2022) - Kwon, Haeun; Nguyen, Quynh Nhu; Ryu, Seung Mok; Kwon, Jaeyoung; Park, Sojung; Guo, Yuanqiang; Hwang, Bang Yeon; Yim, Joung Han; Kim, Jae-Jin; Kang, Ki Sung; Lee, Dongho
Abstract: Estrogen is a vital hormone responsible for the development of the female reproductive system. Hence, estrogen deficiency in menopause increases various symptoms. This study aimed to discover biologically active compounds from an EtOAc-extract of Neopestalotiopsis clavispora culture medium which has previously shown estrogenic activity. A new α-pyrone (1 ) and a new tetramic acid derivative (2 ), together with hymenosetin (3 ) and pestalotiollide B (4 ), were isolated from the extract. The chemical structures of the new compounds were elucidated using MS and NMR spectroscopy, and the absolute configurations were established by quantum mechanical calculations of electronic circular dichroism and gauge-including atomic orbital NMR chemical shift, followed by DP4 + analysis. The isolated compounds were initially tested for their estrogenic activities using MCF-7 estrogen responsive human breast cancer cells. Hymenosetin (3 ) showed estrogenic activity by increasing the proliferation of MCF-7 cells at the concentration of 2.5  μ M via the phosphorylation of estrogen receptor- α . Graphical Abstract: ga1 Highlights: Two new compounds were isolated from Neopestalotiopsis clavispora culture medium. The absolute configurations were established by NMR chemical shift calculations. Hymenosetin (3 ) showed estrogenic activity.